Damage Reduction of Explosively Driven Spallation by Machining V-Notch Rows on the Surfaces of 304 Stainless Steel Plates - HIROE, T.; FUJIWARA, K.; HATA, H.; NATASATO, K.; MIZOKAMI, K. (Engineering Transactions, 2011)
Plane detonation waves generated in the explosive PETN with use of wire-row explosion technique for initiation have been applied to study on spall behaviour for circular plates of 304 stainless steel, and the slanting surface effects on the damage phenomena for conic frustums and circular cones. In this paper, V-notch rows are produced on the free surface of the square plate specimens of the same material and plane shock waves are similarly transferred from the other surface. The cross-sectional observation of tested and recovered specimens shows that remarkable effects on the reduction of spall damages have been achieved in case of appropriate V-notch configurations. The effect seems to come obviously from weakened interaction of release waves due to the dispersion of directions for reflection waves, and a hydro-code. Autodyn 2D/3D has successfully reproduced the experimental results numerically, suggesting a notch parameter chart for spall damage evaluation.